Fabrication and properties of silicene and silicene–graphene layered structures on Ir (111)*Project supported by the National Basic Research Program of China (Grant Nos. 2013CBA01600 and 2011CB932700), the National Natural Science Foundation of China (Grant Nos. 61222112, 61390501, 51325204, 11334006, and 61306114), the Science Fund from Chinese Academy of Sciences (Grant Nos. 1731300500015 and XDB07030100), and the Fundamental Research Funds for the Central Universities, China. (August 2015) - Meng, Lei; Wang, Ye-Liang; Zhang, Li-Zhi; Du, Shi-Xuan; Gao, Hong-Jun
Abstract Silicene, a two-dimensional (2D) honeycomb structure similar to graphene, has been successfully fabricated on various substrates. This work will mainly review the syntheses and the corresponding properties of silicene and silicene–graphene layered structures on Ir (111) substrates. For silicene on Ir (111), the buckled <inline-graphic xlink:href="ark:/27927/pgj2j5w8jnq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> silicene/<inline-graphic xlink:href="ark:/27927/pgj2j5w8k85" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Ir (111) configuration and its electronic structure are fully discussed. For silicene–graphene layered structures, silicene layer can be constructed underneath graphene layer by an intercalation method. These results indicate the possibility of integrating silicene with graphene and may link up with potential applications in nanoelectronics and related areas.